Перспективы исследования экологической футурологии: про иллюзию и предвидение как человеческие способности - Годзь, Наталья Борисовна (НТУ "ХПИ", 2016)
В статье исследуется феномен экологической футурологии. В рамках статьи рассматривается не только феномен предвидения, прогнозирования, но и феномен и действие (как позитивное, так и негативное) иллюзии. Вводится понятие «иллюзорное представление» как отдельный участок механизма конструирования и функционирования механизмов футурологического знания. Исследованием акцентируем и раскрываем необходимость восприятия предвидения не только как «эффекта мгновенности», но и как механизма «мгновенного инсайта», который возникает как следствие длительного интеллектуального труда на научное, ментальное, интеллектуальное постижение потребностей человечества, в том числе и потребностей выживания и развития.

The proposal to review article, continue to study the ecological futurology. Prognostics, planning tend to reduce the effect of risks and surprises. Futurology in this respect is much freer, it on the contrary, can be delegated to the presence of a certain number of prerequisites for the unknown «unidentified future». Material article stresses the need for features and philosophical analysis of the future in the context of the review. As part of the article is considered on only a phenomenon of foresight forecasting, but the phenomenon and effects (both positive and negative) illusion. The notion of «delusional» can be as a separate section of the mechanism construction and operation mechanisms futurological knowledge. The study accentuate and reveal the need for the perception of foresight, not only as the «effect of the moment», but also as a mechanism of «instant insight», which arises as a consequence of a long intellects’ work on the scientific, mental, intellectual comprehension of human needs, including the needs of survival and development.
The prospects to study of ecological futurology: about illusion and foresight as human abilities
Keywords: вопросы футурологии; "эффект мгновенности"; "мгновенный инсайт"; ретрофутурология; ecological futurology; "the effect of the moment"; "instate insight"; retrofuturology